Kerjasama Selatan Selatan dan Triangular Sebagai Sarana Diplomasi Indonesia Secara Global - Jerry Indrawan; Ganis Purnaningtyas; Dede Suprayitno (Jurnal Kewarganegaraan, 2023)
Since the 1955 Asian-African Conference (AAC), Indonesia has been actively involved in South South Triangular Cooperation (SSTC) which serves as a catalyst for political movements in international cooperation because it helps exchange resources and knowledge according to the needs of developing countries. Indonesia has a dual role as a recipient and giver of assistance in SSTC. This study aims to answer issues related to the implementation of SSTC in the Indonesian context. The research method used is descriptive research with a qualitative approach and the data collected by literature study. The results showed that in terms of Indonesia's interests, SSTC helps achieve utilization in bilateral trade and becomes a forum for sharing experiences and encouraging other countries to apply democratic principles. Indonesia provides financial and non-financial support, but is more likely to be in non-financial form. Relevance in this era, the impact of SSTC will be a powerful instrument to reduce dependence on superpowers. SSTC is considered suitable and beneficial for sustainable development, both from an economic, socio-cultural, and political security perspective. Limited capital is the biggest obstacle for SSTC member countries, especially during the outbreak of the Covid-19 pandemic. Keywords: SSTC, Development, G-20 Forum, International Relations